A Review of Solid State Processes in Manufacture of Functionally Graded Materials - Tripathy, Aravind; Kumar Sarangi, Saroj; Kumar Chaubey, Anil (International Journal of Engineering and Technology, 2018)
The demand for materials exhibiting multiple functionalities & having greater relevance to aerospace & other similar applications have led researchers to develop such materials named Functionally Graded Materials, having properties that may be tailored for a definite application. Better stiffness-to-weight ratio characteristic of such material is the main reason of their popularity today. Efforts are also directed to produce such materials in bulks and in a cost-effective manner. An overview of fabrication methods such as Powder metallurgy, Solid Freeform Fabrication, Laser cladding, Selective Laser Sintering, 3-D Printing and Selective Laser Melting etc. are deliberated here. The quality of FGM produced with better awareness, research and patronization at the state level is a continuous process, hence a review of solid state processes in manufacture of Functionally Graded Materials is the need of the hour.Â